Pharmacologically distinct phenotypes of α1B‐adrenoceptors: variation in binding and functional affinities for antagonists. (5th September 2014) - Yoshiki, Hatsumi; Uwada, Junsuke; Anisuzzaman, Abu Syed Md; Umada, Hidenori; Hayashi, Ryoji; Kainoh, Mie; Masuoka, Takayoshi; Nishio, Matomo; Muramatsu, Ikunobu
<x xml:space="preserve">Abstract</x> Background and Purpose The pharmacological properties of particular receptors have recently been suggested to vary under different conditions. We compared the pharmacological properties of the α1B‐adrenoceptor subtype in various tissue preparations and under various conditions. Experimental Approach [3H]‐prazosin binding to α1B‐adrenoceptors in rat liver (segments, dispersed hepatocytes and homogenates) was assessed and the pharmacological profiles were compared with the functional and binding profiles in rat carotid artery and recombinant α1B‐adrenoceptors. Key Results In association and saturation‐binding experiments with rat liver, binding affinity for [3H]‐prazosin varied significantly between preparations (KD value approximately ten times higher in segments than in homogenates). The binding profile for various drugs in liver segments also deviated from the representative α1B‐adrenoceptor profile observed in liver homogenates and recombinant receptors. L‐765, 314 and ALS‐77, selective antagonists of α1B‐adrenoceptors, showed high binding and antagonist affinities in liver homogenates and recombinant α1B‐adrenoceptors. However, binding affinities for both ligands in the segments of rat liver and carotid artery were 10 times lower, and the antagonist potencies in α1B‐adrenoceptor‐mediated contractions of carotid artery were more than 100 times lower than the representative α1B‐adrenoceptor profile. Conclusions and Implications In contrast to the consistent profile of recombinant α1B‐adrenoceptors, the pharmacological profile of native α1B‐adrenoceptors of rat liver and carotid artery varied markedly under various receptor environments, showing significantly different binding properties between intact tissues and homogenates, and dissociation between functional and binding affinities. In addition to conventional 'subtype' characterization, 'phenotype' pharmacology must be considered in native receptor evaluations in vivo and in future pharmacotherapy.